DAMPAK KEBIJAKAN TATANIAGA PUPUK TERHADAP PERAN KOPERASI UNIT DESA SEBAGAI DISTRIBUTOR PUPUK - NYAK ILHAM (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2001)
Fertilizers marketing policy that have been decided by the government on December 1998 isaimed at creating opportunity for suppliers or importers to supply and distribute fertilizers forthe farmers. The problem is that the Cooperation of Village Unit Cooperation (KUDs) asdistributors at Lini-IV will compete with supplier or importer who has more capital and goodmanagement. The aim of this paper is to asses the impact of zero subsidies and free marketpolicy of fertilizers distribution system and the performance of Cooperation of Village UnitCooperation (KUDs). This research has been carried out by the Center for Agro-socioEconomic Research (CASER), by taking Karawang and Subang (West Java) as cases. Theprimary data were collected from PT. Pusri, SP. Bimas of Department of Agriculture,Fertilizer Retailers and Cooperation of Village Unit Cooperation (KUDs). The secondarydata were collected from PT. Pusri. The finding of this research shows that, after theimplementation of the policy, fertilizer distribution system becomes shorter (simpler) andfertilizers are distributed through many channels, so that farmers can buy fertilizers easily andat relatively low prices. Because of capital constraint, KUDs can not compete with nonCooperation of Village Unit Cooperation (non-KUDs) distributors. Consequently, the sale ofKUDs fertilizers had decreased, and this condition will disturb the survival of Cooperation ofVillage Unit Cooperation (KUDs) as a distributors. In the long run, government must beaware of the possibility that non Cooperation of Village Unit Cooperation (non-KUDs)distributors form a cartel and have strong power in fertilizer marketing. To stabilize thecontribution of Cooperation of Village Unit Cooperation (KUDs) as public institution infertilizer distribution activity, government needs to empower Cooperation of Village UnitCooperation (KUDs) through increasing working capital and coordinating fertilizerdistribution mechanism through Center of Village Unit Cooperation (PUSKUDs).